Answers

2014-02-21T22:46:35+01:00
2014-02-23T00:42:12+01:00
                                                                                                                                                                                 using the formula c²=a²+b²                                                                                   

using pythagoras theorem we have: c²=a²+b²  
dividing both sides by c² ,we have 1=a²/c²+b²/c²
 sinA=a/c and cosA=b/c 
sin²A+cos²A=1  
NOTE:sin²A≡sinA²             same thing goes with cos²A
  dividing  the LHS and the RHS of the identity above , we have:
 sin²A/sin²A+cos²A/sin²A=1/sin²A 
 1+cot²A=cosec²A                                                                                                                                                                                     

  
0